2020
DOI: 10.3390/agronomy10091340
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Pile Burn on N Dynamic and N Loss in Mediterranean Croatia

Abstract: There is a lack of information in the rural Mediterranean area about agricultural pile burning impacts on soil nitrogen (N) dynamic and the N loss. Therefore, this research aims to study the impacts of moderate (MS), and high (HS) severity burn on N transformation and N losses, compared to an unburned (C) during the first year. The experimental plots (10 m2) were established in Croatia (43°58′ N 15°31′ E), in a slope ~18°, with a southwest exposition. Five days after the burn, C treatment had a significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In addition, our burn scars were located in a riparian zone where sediments and organic matter can be deposited during minor flooding events or from upslope erosion. These processes can also be accelerated by site‐level burning (Santín & Doerr 2016; Delač et al 2020), which occurred twice during our study. Fourth, previous studies have predominately occurred in conifer‐dominated ecosystems where rates of passive vegetation recovery may differ relative to Midwestern oak woodlands, due to differences in vegetation, soils, climate, and management practices.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, our burn scars were located in a riparian zone where sediments and organic matter can be deposited during minor flooding events or from upslope erosion. These processes can also be accelerated by site‐level burning (Santín & Doerr 2016; Delač et al 2020), which occurred twice during our study. Fourth, previous studies have predominately occurred in conifer‐dominated ecosystems where rates of passive vegetation recovery may differ relative to Midwestern oak woodlands, due to differences in vegetation, soils, climate, and management practices.…”
Section: Discussionmentioning
confidence: 65%
“…Ammonium (NH 4 -N) and nitrate (NO 3 -N) are the plant-available forms of nitrogen, and are generated via the decomposition of organic N compounds [ 39 ]. Previous studies [ 40 , 41 , 42 ] have reported high NH 4 -N concentrations after high-severity burning, whereas NO 3 -N did not form directly through heating [ 43 ], but was produced after burning through the nitrification of NH 4 -N [ 44 ]. This might explain the significant decrease in NO 3 -N of the paddy soils after burning ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increase in magnitude and frequency of phenomena such as fires and floods as a result of global change, only a few articles (six and four respectively) have analyzed the impact of these phenomena on vegetation. In the articles related to the fire topic, the main environmental factors that determine severity affecting forest formations located in Mediterranean Basin have been identified and evaluated [146][147][148][149][150]. The studies relating to flood effects on vegetation dealt with flooding risk analysis, assessed on different vegetation types by simulations and models [121,151], by reconstructions of flash floods tree-ring based [152] and by sustainable tools to mitigate urban flood risk [123].…”
Section: Extreme Rainfall Events In Mediterranean Basin: Impacts On V...mentioning
confidence: 99%